Russian Models from the Mechanisms Collection of Bauman University - Golovin, A.; Tarabarin, V.; SpringerLink (Online service) (Dordrecht : Springer Netherlands : Imprint: Springer, 2008)
The collection of the Theory of Mechanisms Department of Bauman University contains more than 500 mechanisms models. Founded in the 1930s, the first exhibits were models from the collections of Redtanbacher, Voight, and Reuleaux. Later the collection expanded through the addition of models created or manufactured by Russian specialists. Today these models form an essential and considerable part of the collection which includes models of which only one to three copies exist in the world. The subject material of this book is largely unknown, but of great interest to engineers and scientists, mechanics, and historians of technology. The book also contains information about the history of Bauman university, the TMM department and the Russian specialists who created the collection to give a complete overview of this unique collection and the history of its creation. Indexed in the Book Citation Index– Science (BKCI-S).
“Applied Mechanics” – TMM in Bauman University -- History of Applied Mechanics Cabinet and Mechanisms Collection -- Russian Models in the Bmstu Mechanisms Collection.
Keywords: Machinery; Engineering design; Control engineering; Robotics; Mechatronics; Mechanics; History; Philosophy; Machinery and Machine Elements; Engineering Design; Control, Robotics, Mechatronics; Classical Mechanics; History of Science; Philosophy of Technology